Alignment of technology development plans in the oil industry of developing countries: The case of Iran. (June 2022) - Ghazinoory, Sepehr; Hoshdar, Fatemeh; Nozari, Maryam
Abstract: Technology development plays a significant role in the petroleum industry. In countries where all oil activities are carried out under the supervision of the National Oil Company, technology development must be done at the industry level. The development of technology at the industry level requires careful planning at different layers of the industry. Systematic planning and alignment at different levels of plans are essential factors for success in this regard. At each level of the industry, certain conditions and requirements, technology strategies, interactions among stakeholders at different levels, and technology priorities affect each other through bilateral relations between different levels of the industry. This interaction necessitates the existence of alignment between them. This study aims to discover different aspects of technology planning with two famous techniques of roadmapping (TRM) and quality function deployment (QFD) and provide a model to ensure the alignment in technology plans of the oil industry of developing countries and to this end, the Iranian oil industry is studied as a case. The current model maintains the interrelationship between the strategic technology fields of the industry and technology priority applications in major companies as well as putting the future technology needs in the technology portfolio of the industry. Meanwhile, it provides a platform for managers to identify the priorities of companies and form learning circles‌ to participate in the development of higher technology programs. Highlights: Alignment in different levels of plans are essential factors for technology development at the oil industry level. TRM & QFD provided a model to ensure the alignment in technology plans in the Iranian oil industry. Our model maintains the interrelationship between the strategic technology fields of main companies.